(untitled) (International journal of artificial intelligence, 2026)
This article scientifically and analytically examines the development trends of the cashless payment system as an essential component of the digital economy in Uzbekistan and its impact on the country’s Gross Domestic Product (GDP). The study substantiates that the increasing volume of transactions conducted through electronic payment systems, mobile banking services, QR payments, and plastic cards has become one of the key factors accelerating economic activity. Furthermore, the expansion of cashless payments contributes to financial transparency, reduces the share of the shadow economy, and enhances the stability of tax revenues. Based on statistical data, the article evaluates the recent dynamics of digital payment infrastructure development in Uzbekistan and explains its influence on macroeconomic indicators. The research findings indicate that the expansion of cashless economic relations serves as a strategic factor supporting sustainable economic growth in the country.